The Risk For Malignancy of the Thyroid Nodule is Modulated by Gender, Echotexture, and Intranodular Lymphocytic Thyroiditis - Arena, Salvatore; Benvenga, Salvatore (Hormone and Metabolic Research, 2019)
Based on the American (Bethesda, 2017) or Italian (SIAPEC 2014) cytological categories of thyroid nodules, the risk of malignancy and management vary. This risk is 5–10% or<3% (benign or TIR2), 6–18% or<10% (AUS/FLUS or TIR3A), 10–40% or 15–30% (FN/SFN or TIR3B), 45–60% or 60–80% (suspicious or TIR4), 94–96% or 95% (malignant or TIR5). In 408 thyroid nodules evaluated cytologically, we computed the malignancy rate in each category considering gender (325 females, 83 males), echotexture (268 isoechoic, 140 hypoechoic), intranodular chronic lymphocytic thyroiditis (ICLT: 113 with and 295 without); histology (263 benign, 145 malignant). It was 0–1.7% for the benign categories, except hypoechoic/ICLT+ve nodules of females (25%); 0–2.3% for the AUS/FLUS category, except isoechoic/ICLT–ve nodules of males (11.1%) and hypoechoic/ICLT–ve nodules of females (22.2%). For the FN/SFN category, rate was the most variable (from 0% in isoechoic/ICLT+ve nodules of males to 100% in hypoechoic/ICLT–ve nodules of males). The 30% threshold for risk was passed in four subgroups, and the 40% threshold in two subgroups (45% in isoechoic/ICLT–ve nodules of males, 80% in hypoechoic/ICLT+ve nodules of females). For the suspicious category, rate was 100% in males, except those with isoechoic/ICLT–ve nodules (75%), and>80% in females with hypoechoic nodules. For the malignant category, rate was always 100%. In conclusion, particular groups of nodules (based on gender, echotexture, and ICLT) within the cytologically benign through the suspiciously malignant category are at risk of malignancy substantially greater (even 100%) than the standard one. Accordingly, the suggested management cannot be standardized.
Keywords: chronic lymphocytic thyroiditis; thyroid cancer; thyroid fine-needle aspiration cytology; thyroid ultrasonography